Credibility of disability estimates from the 2011 population census in Poland - Elżbieta Gołata; Grażyna Dehnel (Statistics in Transition New Series, 2021)
The problem of disability is perceived as one of the most serious social issues faced by the contemporary society. The number of people with disability is consistently rising for a variety of reasons, including the aging of the population. Data on disability are collected through numerous statistical surveys, among which censuses are the most wide-scale ones. In the period between the 2002 and 2011 censuses (the last two censuses conducted in Poland), a 14% decrease in the number of people with disabilities was observed. However, it should be emphasised that significant modifications were introduced to the methodology of the last census. Population census 2011 was the first census in Poland combing administrative data sources and the survey sampling method. The main objective of the study is to assess the quality of estimates relating to the number of disabled persons, obtained on the basis of the 2011 census data. It is a comparative study aimed at identifying the similarities and discrepancies between the estimates, and determining the size and source of these discrepancies. The analysis takes into account such aspects as the measurement methods, the definitions and criteria of disability, the voluntary nature of the question, and the quality of the information on disability obtained from various sources.
Keywords: I15; I18; J11; J14; 519; disability; health condition; demographic processes; quality of a statistical survey